2021
DOI: 10.1029/2020gl090905
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Synchronization of Lee Vortices in Geophysical Wakes

Abstract: Wake vortices in tidally modulated currents past a conical hill in a stratified fluid are investigated using large‐eddy‐simulation. The vortex shedding frequency is altered from its natural steady‐current value leading to synchronization of wake vortices with the tide. The relative frequency (f*), defined as the ratio of natural shedding frequency (fs,c) in a current without tides to the tidal frequency (ft), is varied to expose different regimes of tidal synchronization. When f* increases and approaches 0.25,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…When trueS1 $\overline{S}\ll 1$, the tide‐associated momentum loss is negligible and the influence of tidal forcing on the shed wake vortices may be insignificant. At R = 1, tidal synchronization is observed (Puthan et al., 2021). The behavior at lower values of R (and trueS $\overline{S}$) remains to be ascertained.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…When trueS1 $\overline{S}\ll 1$, the tide‐associated momentum loss is negligible and the influence of tidal forcing on the shed wake vortices may be insignificant. At R = 1, tidal synchronization is observed (Puthan et al., 2021). The behavior at lower values of R (and trueS $\overline{S}$) remains to be ascertained.…”
Section: Theorymentioning
confidence: 99%
“…Thus, we focus on the role of varying the relative amplitude of tidal velocity (R) in the emergence of transient eddies in Section 4, and the attendant dissipation in the wake and the hydraulic response region in Section 5. Puthan et al (2021) showed that in a tidally modulated flow with R = 1 and Ω s,c /Ω t = 5/6, downstream wake vortices are found at frequencies that differ from both the tidal frequency Ω t and the natural shedding value Ω s,c . Instead, the frequency of the wake vortices was found to be Ω t /2, a value smaller than both Ω t and Ω s,c .…”
Section: Simulation Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Turbulent wakes are ubiquitous both in nature and man-made devices. From flow past moving vehicles (Grandemange et al 2015) to flow past topographic features (Puthan, Sarkar & Pawlak 2021) in oceans, they play an important role in transporting momentum and energy across large distances from the wake generator. In the ocean and the atmosphere, the background density often has a stable density stratification.…”
Section: Introductionmentioning
confidence: 99%